1996
DOI: 10.1111/j.1439-0442.1996.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Soybean and Cowpea on Gut Morphology and Faecal Composition in Creep and Noncreep‐fed Pigs

Abstract: The effects of creep feeding and different levels of soybean meal (SBM) and cowpea meal on the intestinal morphology and faecal characteristics were investigated in weaners. Prior to the feeding trial, one group of piglets was creep-fed and the other noncreep-fed. The two groups of piglets were weaned at 28 days and randomly assigned to four different diets whose main sources of protein were: T,-skimmed milk powder (control); T2-31 % soybean meal; T3-15 % soybean meal and 12 % skimmed milk powder; and T, -lOO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Similar results have been reported by Montagne et al (2004) who found no significant effect on the proliferation of ETEC when animal protein was replaced with plant protein in a rice-based diet. Several studies have shown a decrease in villous height in newly weaned pigs fed a diet with a high level of soya instead of DSMP (Li et al, 1991;Makinde et al, 1996), while others have failed to do so (McCracken et al, 1999;Jiang et al, 2000). The fact that pigs fed the DSMP diets ate significantly more than those fed the SOYA diets (see Wellock et al, 2008), and that DSMP constituted only 25% of total protein in the DSMP diets, may explain why there was no significant effect of protein source on ETEC shedding or measures of enteric health.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by Montagne et al (2004) who found no significant effect on the proliferation of ETEC when animal protein was replaced with plant protein in a rice-based diet. Several studies have shown a decrease in villous height in newly weaned pigs fed a diet with a high level of soya instead of DSMP (Li et al, 1991;Makinde et al, 1996), while others have failed to do so (McCracken et al, 1999;Jiang et al, 2000). The fact that pigs fed the DSMP diets ate significantly more than those fed the SOYA diets (see Wellock et al, 2008), and that DSMP constituted only 25% of total protein in the DSMP diets, may explain why there was no significant effect of protein source on ETEC shedding or measures of enteric health.…”
Section: Discussionmentioning
confidence: 99%
“…The trypsin inhibitor activity for the cowpea variety in the present study was generally higher than those reported for other cowpea varieties (OLOGHOBO and FETUGA 1984). Marked effects on intestinal histomorphometry due to feeding with raw cowpea have been shown to lead to enteropathology which were implicated in low growth performance in pigs (MAKINDE et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, like most other legumes, cowpeas contain antinutritional factors (ANFs) (MAKINDE et al 1996). It has also been shown that feeding raw cowpea causes reduced growth and histomorphometric changes in the various segments of the intestine (MAKINDE et al 1997) attributable to ANFs.…”
Section: Introductionmentioning
confidence: 98%
“…Cowpeas (Vigna unguiculata) like most other legumes have been shown to contain various antinutritional factors such as trypsin inhibitors, lectins and tannins (Gatehouse and Boulter, 1983;Mnembuka and Eggum, 1995) that are known to have deleterious effects on the growth performance, body composition and gastrointestinal systems (Grant et al, 1995;Makinde et al, 1996). However, the effects of most of the antinutritional factors can be minimized and even neutralized by various processing methods such as moist or dry heat treatment and fermentation (D'Mello, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of most of the antinutritional factors can be minimized and even neutralized by various processing methods such as moist or dry heat treatment and fermentation (D'Mello, 1995). Given the shortage of protein sources in the arid regions, cowpea, which is a drought resistant crop, can go a long way toward meeting the demands for plant protein in the arid regions and also the search for novel legumes (Makinde et al, 1996).…”
Section: Introductionmentioning
confidence: 99%